The impact of Ramadan intermittent fasting on anthropometric measurements and body composition: Evidence from LORANS study and a meta-analysis - Al-Jafar, Rami; Wahyuni, Nisa Sri; Belhaj, Karim; Ersi, Mohammad Hamed; Boroghani, Zahra; Alreshidi, Amer; Alkhalaf, Zahra; Elliott, Paul; Tsilidis, Konstantinos K.; Dehghan, Abbas (Frontiers in Nutrition, 2023)
Background- Although the effect of Ramadan intermittent fasting (RIF) on anthropometry and body composition has been questioned, none of the previous studies tried to explain the reported changes in these parameters. Also, systematic reviews that investigated the topic were limited to healthy individuals or a specific disease group. Methods- The London Ramadan Study (LORANS) is an observational study on health effects of RIF. We measured weight, waist circumference (WC), hip circumference (HC), body mass index (BMI), waist-to-hip ratio (WHR), basal metabolic rate (BMR), fat percentage (FP), free-fat mass (FFM), extremities predicted muscle mass, total body water (TBW), trunk FM, trunk FFM and trunk predicted muscle mass before and immediately after Ramadan. Using mixed-effects regression models, we investigated the effect of RIF with adjustment for potential confounders. We also conducted a meta-analysis of the results of LORANS with other studies that investigated the effect of RIF on anthropometry and body composition. The review protocol is registered with PROSPERO registry (CRD42020186532). Results- We recruited 146 participants (Mean±SD age =43.3±15 years). Immediately after Ramadan, compared with before Ramadan, the mean difference was -1.6 kg (P < 0.01) in weight, -1.95 cm (P < 0.01) in WC, -2.86 cm (P < 0.01) in HC, -0.60 kg/m2 ( P < 0.01) in BMI and -1. 24 kg (P < 0.01) in FM. In the systematic review and meta-analysis, after screening 2150 titles and abstracts, 66 studies comprising 7,611 participants were included. In the general population, RIF was followed by a reduction of 1.12 Kg in body weight ( -1.89 to -0.36, I2=0), 0.74 kg/m2 reduction in BMI (-0.96 to -0.53, I2=0), 1.54 cm reduction in WC( -2.37 to -0.71, I2=0) and 1.76 cm reduction in HC (-2.69 to -0.83, I2=0). The effect of fasting on anthropometric and body composition parameters starts to manifest in the second week of Ramadan and starts to diminish three weeks after Ramadan. Conclusion-RIF is associated with a reduction in body weight, BMI, WC, HC, FM, FP and TBW. Most of these reductions are partially attributed to reduced FM and TBW. The reductions in these parameters appear to reverse after Ramadan.